RESILIÊNCIA INCORPORADA ÀS PRÁTICAS DOCENTES COM ADOLESCENTES - BARBOSA DOS ANJOS, ALYNE; LOPES GUEDES, BIANCA; BRAGANÇA DA SILVA, DAIANNE; PEREIRA MARQUES, SABRINA; FERREIRA MENDES, YARA (Sinapse Múltipla, 2019)